African Initiated Churches of the Spirit and Pneumatology - Anderson, A. (Word & World, 2003)
he independent African “churches of the Spirit,” perhaps the majority of African Initiated Churches (AICs) today, like worldwide Pentecostalism, practice gifts of the Spirit like healing, prophecy, and speaking in tongues. Because of their “Spirit” manifestations and pneumatological emphases and experiences, earlier studies of these churches considered them “syncretistic,” “post-Christian,” and “messianic” groups. Understanding the pneumatology of these movements is crucial, as part of the problem that Western observers had with the churches of the Spirit had to do with their understanding of the Holy Spirit. This was often seen as accommodating the pre-Christian past, and was thought to be particularly linked with divination, ancestor rituals, and the like. Some European observers spoke of these churches as having “misunderstood” the Holy Spirit.
Free
Keywords: African independent churches; Holy Spirit; Theology – Africa; Theology; Contextual